An allergic bullous drug reaction triggered by levofloxacin and trimethoprim/sulfamethoxazole mimicking an autoimmune blistering disease - Ana Maria Abreu Velez; A. Deo Klein; Michael S. Howard (Our Dermatology Online, 2012)
Introduction: Allergic drug reactions represent common clinical challenges. Selected allergic drug reactions present with blisters.Case report: A 73 year old female was prescribed levofloxacin injection and trimethoprim/sulfamethoxazole for a urinary tract infection. Subsequently, the patient developed blisters on both of her hands and feet, associated with clinical pruritus. Clinically, bullae were observed on both of her palms and soles, associated with erythema.Methods: Biopsies for hematoxylin and eosin (H&E) examination, as well as for direct immunofluorescence (DIF) were performed.Results: Focal areas of the epidermis displayed diffuse, mild spongiosis. An acute inflammatory process extended into hair follicular units, with focal rupture of these structures. Focal subepidermal vesiculations were also noted in the areas of follicular unit rupture. DIF examination demonstrated faint linear deposits of anti-human fibrinogen at the basement membrane zone of the skin, as well as around several hair shafts. A similar fibrinogen deposition pattern also present around the upper dermal blood vessels.Conclusion: In our practice experience, the most common cause of blistering diseases are allergic drug reactions, in contradistinction to primary autoimmune blistering disorders. Clinical physicians, pathologists and immunodermatologists should be aware that allergic drug reactions can mimic primary autoimmune blistering disorders, both clinically and in selected immunologic aspects.